2015
DOI: 10.1515/nsad-2015-0027
|View full text |Cite
|
Sign up to set email alerts
|

Justifications of national gambling policies in France and Finland

Abstract: Aims The principles of free trade and free circulation of services within the European Union have created pressures to make the strictly controlled European gambling markets more open. According to the Court of Justice of the European Union, restrictions on gambling are only allowed if they are justified in admissible terms of consumer protection, prevention of criminal activity and protection of public order. This study compares the gambling laws of two European societies, France and Finland, to analyse how t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 15 publications
(7 reference statements)
1
15
0
1
Order By: Relevance
“…The position of VR and Alko had already seen some derogations before the analyzed period, but Veikkaus has remained the sole provider of all gambling products in Finland and the analysis showed a strong political will to maintain and to further consolidate this monopoly policy. The scrutiny of the European Union institutions in the Finnish gambling policy particularly following the 1999 CJEU ruling in the Läära case and the infringement proceedings closed in 2013 further evoked some fears that the EU would transfer competencies in the field of gambling to Brussels (also Littler, 2011;Marionneau, 2015). It is likely that one of the reasons behind the merger of the Finnish gambling operators was also to prevent further scrutiny.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The position of VR and Alko had already seen some derogations before the analyzed period, but Veikkaus has remained the sole provider of all gambling products in Finland and the analysis showed a strong political will to maintain and to further consolidate this monopoly policy. The scrutiny of the European Union institutions in the Finnish gambling policy particularly following the 1999 CJEU ruling in the Läära case and the infringement proceedings closed in 2013 further evoked some fears that the EU would transfer competencies in the field of gambling to Brussels (also Littler, 2011;Marionneau, 2015). It is likely that one of the reasons behind the merger of the Finnish gambling operators was also to prevent further scrutiny.…”
Section: Discussionmentioning
confidence: 99%
“…Only at this point does consumer protection come up in the discussion, despite its status as the main official justification for the gambling monopoly (Marionneau 2015). A representative of the helpline for problem gamblers, Peluuri, (25.2.2015) points out that while the monopoly is officially justified in terms of preventing gambling harms, the discussion only centres around competition.…”
Section: Gamblingmentioning
confidence: 99%
“…While such measures have been implemented in some jurisdictions -including limitations on availability in Norway, Russia and several Eastern and Central European countries, and the increasing amount of limit setting and pre-commitment tools available particularly in online environments (Auer, Reiestad, & Griffiths, 2020) -actual policies are often quite different from 'optimal' policies'. This has been attributed to the difficulty in changing established regulatory patterns (Marionneau, 2015) as well as financial interests and path dependencies that prevent the regulator from implementing effective policies of problem prevention, as these will impact revenues (Borrell, 2008;Egerer et al, 2018a;Paldam, 2008).…”
Section: The Regulation Of Gambling Economicsmentioning
confidence: 99%
“…However, research looking at the social structures behind gambling has had a marginal position in a field that has been strongly focused on methodological and theoretical individualism. This has not only been true of the dominant position of biopsychological views which approach problem gambling as a mental or behavioural disorder, but also of economic theories portraying the act of gambling as consumption (see Aasved, 2003;Marionneau, 2015). This individualist approach has affected how we view problem gamblers, and also how we consider gambling provision or even gambling research (cf., the recent debate on whether gambling is a capitalist conspiracy (e.g., Delfabbro & King, 2017;Livingstone et al, 2018)).…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Nordic Studies on Alcohol and Drugs the latter circumstance of a cultural internalisation is demonstrated by Egerer and Marionneau's (2019) article on cultures and the convenience of gambling among Finnish and French gamblers. Their study shows that the activity has a different cultural position in the two countries: the internalising into gambling belongs in Finland to the sphere of everyday life, but in France it is connected with the peculiarities of the casino environment (see also Marionneau, 2015). This makes gambling such an intriguing case for cultural studies.…”
mentioning
confidence: 99%